Experimental investigation of the earthquake response of a model of a marble classical column. - Mouzakis, H.P (Earthquake engineering & structural dynamics.)
Experimental results concerning the earthquake response of a marble model of a classical column and reported herein. The model was a 1: 3 scale replica of a column of the Parthenon on the Acropolis of Athens, made from the same material as the original. Several earthquake motions, scaled appropriately in order to cause significant rocking but no collapse of the column, were used as the excitation. The base motion was applied in plane (in one horizontal and the vertical direction) or in space (in two horizontal and the vertical direction), using the shaking table facility at the Laboratory for Earthquake Engineering of the National Technical University of Athens. It was found that the column might undergo large deformations during the shaking, which are not necessarily reflected by the residual displacements at the end of it. For planar excitations, significant out of plane displacements can happen, triggered by the inevitable imperfections of the specimen. It was also verified that the response is very sensitive, even to small changes of the geometry or the input motion parameters. For this reason, the experiments were not repeatable and 'identical' experiments produced different results.